Impact of coupled support on the Romanian dairy cow and buffalo cow sector: A regional profile analysis - Mariana Grodea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The coupled support is a production limiting system, which is granted under the form of an annual payment, to those sectors or regions in a Member State, where certain types of agriculture or certain agricultural sectors, which are very important from economic, social or environmental reasons, are affected by certain difficulties. In the year 2019, at EU 28 level, the largest amount of coupled support payments was allocated to the livestock farming sector (73.2%), out of which 20.1% to the dairy sector. In Romania, the dairy sector was allocated the amount of 88 million euros, i.e. 59.1% of total livestock sector. The obtained results highlight that the impact of the scheme application is not significant as regards the sector development, having in view that the share of cows and buffaloes authorised for payment in total herds ranged from 7.1% in 2015, 9.2% in 2016, 18.6% in 2017to 22.5% in 2018.
Keywords: Q10; Q13; Q19; 330; dairy cows; buffalo cows; coupled support; production